2013
DOI: 10.13107/jocr.2250-0685.123
|View full text |Cite
|
Sign up to set email alerts
|

Extra skeletal Soft Tissue Ewing’s Sarcoma with Variant Translocation of Chromosome t (4; 22) (q35; q12)-A Case Report

Abstract: Introduction:Ewing’s sarcomas is a rare primitive neuroectodermal tumour (PNET) which has an annual incidence of 2.9 /million population in USA 1Jeffery Toretsky et al (2008) They are very uncommon in African and Asian population. It is commonly associated with reciprocal translocation between chromosome 11 and 12 t (11:12) or less frequently the t(21;22)(q22;ql 2) translocation. It is highly aggressive tumor which is PAS- and CD99 (MIC2)-positive relatively few variant translocations have been reported in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Relevant to the second case highlighted, a t(4;22)(q35;q12) reciprocal translocation, it has previously been reported, by conventional chromosome analysis, in an extra-skeletal soft tissue (the distal aspect of right thigh) ES in a patient who presented with pulmonary metastases and paraplegia due to involvement of the spine [ 20 ]. However, FISH or other molecular diagnostic methods for an EWSR1::FLI1 fusion was not performed [ 20 ]. Interestingly, a t(4;22)(q35;q12) translocation has also been reported in a case of embryonal rhabdomyosarcoma and results in the fusion of the EWSR1 gene with the DUX4 gene [ 21 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Relevant to the second case highlighted, a t(4;22)(q35;q12) reciprocal translocation, it has previously been reported, by conventional chromosome analysis, in an extra-skeletal soft tissue (the distal aspect of right thigh) ES in a patient who presented with pulmonary metastases and paraplegia due to involvement of the spine [ 20 ]. However, FISH or other molecular diagnostic methods for an EWSR1::FLI1 fusion was not performed [ 20 ]. Interestingly, a t(4;22)(q35;q12) translocation has also been reported in a case of embryonal rhabdomyosarcoma and results in the fusion of the EWSR1 gene with the DUX4 gene [ 21 ].…”
Section: Discussionmentioning
confidence: 95%
“…The t(4;22)(q35;q12) reciprocal translocation in our case involved the distal (near sub-telomere) region of the long arm of chromosome 4 at the 4q35 band, resulting in a cryptic t(4;11;22)(q35;q24;q12) three-way translocation by conventional chromosome analysis. The previously reported ES case with a t(4;22)(q35;q12) reciprocal translocation by conventional chromosome analysis [ 20 ] may also have a cryptic t(4;11;22)(q35;q24;q12) three-way translocation leading to an EWSR1::FLI1 fusion. Therefore, performing FISH or gene fusion-based assays for an EWSR1::FLI1 fusion in these ES cases is vital to rule out a cryptic three-way translocation or other complex rearrangements.…”
Section: Discussionmentioning
confidence: 99%
“…In 85% of EES, a reciprocal translocation between chromosomes 11 and 22 is present, specifically t (11; 22) (q24; q12) resulting in the EWSR1-FLI1 gene [ 7 , 14 , [27] , [28] , [29] ]. About 10% of cases possess a translocation of t (21;22) (q22; q12) to produce the EWSR1-ERG gene [ 4 , [30] , [31] , [32] ]. Both of these chimeric genes encode proteins that induce aberrant oncogenic factors [ 14 , 19 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has not been any evidence of familial or environmental influence. [11][12][13][14] Radiographs may demonstrate a nonspecific soft-tissue mass in proximity to a bone without gross osseous involvement. 9,15,16 Computed tomography (CT) usually shows a soft tissue mass with similar attenuation as skeletal muscle (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, genetic studies have demonstrated reciprocal translocation of t(11; 22)(q24; q12) in approximately 95% of patients, with the remainder demonstrating t(21; 22) (q22; q12) translocation. 11 12 Generally, these tumors are commonly seen in the paravertebral regions or in the deep soft tissues of the extremities, with lower extremities having a higher propensity than upper extremities. 9 Patients with EES often note a rapidly growing soft-tissue mass, with about one-third being painful secondary to compression of adjacent structures.…”
Section: Discussionmentioning
confidence: 99%